Thirty years of Black education (1953-1983) with special emphasis on aims (an historical - educational appraisal) - Themane, Mahlapahlapana Johannes (My University, 1989)
Refer to the document
Thesis (M.Ed.) --University of the North, 1989
Keywords: Black education; Blacks -- Education; Blacks -- South Africa; Education -- History